2021
DOI: 10.1186/s12985-021-01634-9
|View full text |Cite
|
Sign up to set email alerts
|

First molecular characterization of poxviruses in cattle, sheep, and goats in Botswana

Abstract: Background Poxviruses within the Capripoxvirus, Orthopoxvirus, and Parapoxvirus genera can infect livestock, with the two former having zoonotic importance. In addition, they induce similar clinical symptoms in common host species, creating a challenge for diagnosis. Although endemic in the country, poxvirus infections of small ruminants and cattle have received little attention in Botswana, with no prior use of molecular tools to diagnose and characterize the pathogens. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This emphasizes the need to use differential diagnosis that can detect co-infection, even when the direct detection method identifies a primary pathogen [ 59 , 60 , 61 ]. The application of such tools has previously enabled the identification of PCPV in LSD suspicions in Zambia and Botswana, revealing, for the first time, the presence of these pathogens using molecular tools and genomic approaches [ 42 , 43 ]. In Brazil, the co-infection of poxviruses such as VACV and Orf virus (ORFV), VACV and PCPV, or even the triple infection of the bovine papular stomatitis virus (BPSV), PCPV, and VACV has been reported in Bovine based on serological and molecular methods [ 35 , 40 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the need to use differential diagnosis that can detect co-infection, even when the direct detection method identifies a primary pathogen [ 59 , 60 , 61 ]. The application of such tools has previously enabled the identification of PCPV in LSD suspicions in Zambia and Botswana, revealing, for the first time, the presence of these pathogens using molecular tools and genomic approaches [ 42 , 43 ]. In Brazil, the co-infection of poxviruses such as VACV and Orf virus (ORFV), VACV and PCPV, or even the triple infection of the bovine papular stomatitis virus (BPSV), PCPV, and VACV has been reported in Bovine based on serological and molecular methods [ 35 , 40 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although PCPV and other parapoxviruses of cattle are known to occur worldwide, there is little molecular evidence and sequence information regarding PCPV in Africa. Recently, Zambia and Botswana have described molecular PCPV for the first time [ 42 , 43 ]. However, in Nigeria, no molecular information is available.…”
Section: Introductionmentioning
confidence: 99%
“…The gene that specifically targets LSDV is LSDV-ORF010, which has the unique species-specific nucleotide differences. Subsequently, Modise et al (2021) found on this basis that the type of virus can be analyzed by the high-resolution melting (HRM) assay of PCR amplification products generated after genus-specific primers amplify sample viral DNA and bind dyes. Some farms do not have expensive and high-precision instruments, such as PCR machines, and the staff that on the farm may not have the skills to operate PCR machines, so a cheaper, convenient, reliable and easy-to-operate method is needed to replace PCR.…”
Section: Research Advances On the Diagnostic Methods Of Lsdmentioning
confidence: 99%
“…Poxviruses are complex, linear, enveloped, doublestranded DNA viruses with large genomes [48], which are responsible for several economically significant zoonotic diseases affecting humans, wildlife, farm animals, and domestic animals [23]. They belong to the Poxviridae family, which is divided into two subfamilies: Entomopoxvirinae, which infect invertebrates, and Chordopoxvirinae, which infect vertebrates [30,42,45].…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the Poxviridae family, which is divided into two subfamilies: Entomopoxvirinae, which infect invertebrates, and Chordopoxvirinae, which infect vertebrates [30,42,45]. Among the Chord poxvirus subfamily, Capripoxvirus is capable of infecting the cattle, sheep, and goats, which is comprised of goat pox virus (GTPV), sheep pox virus (SPPV), and LSDV and Parapoxvirus [5,16,21,48,72].…”
Section: Introductionmentioning
confidence: 99%